How important is tourism for the international transmission of cyclical fluctuations? Evidence from the Mediterranean - Fabio Canova; Pietro Dallari (European Central Bank (ECB), 2013)
We quantify the importance of the tourism channel for the international transmission of cyclical fluctuations to the Mediterranean basin. We use five destination countries and a number of source countries to provide broad evidence on the link. Source country output shocks produce important fluctuations in international tourism flows. Absent the tourism channel, the output effects in a typical destination country would be reduced by about one-fourth. Imported shocks account for an important portion of the fluctuations in destination countries variables. Policy prescriptions are discussed.
Keywords: E32; C32; 330; Bayesian random coefficient VARs; International Business Cycles; Mediterranean basin; Tourism flows